THE EFFECT OF STORAGE TIME ON THE QUALITY OF ARTIFICIAL FEED FOR FEMALE COBIA FISH (Rachycentron canadum) - Asmanik Asmanik; Akhmad Murtadho; Margie Brite; Putut Har Riyadi (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2022)
The purpose of the study was to determine the quality of artificial feed after the storage process. There are two types of artificial feed: P1 feed (n-3 HUFA content 2.82% dry weight) and P2 feed (n-3 HUFA content 2.76% dry weight). The formula feed was made of isoprotein (43%), isolipid (16%), and isoenergy (417 kcal/100 g). Parameters observed were physical changes (color, odor, texture, broken pieces, fungal infestation, and overall quality); results of proximate and fatty acid analysis after two months of closed storage in plastic bags at 17 °C. Observation of physical parameters showed that the physical condition of both types of feed was good, but P1 feed is more crumbly than P2 feed. The results of proximate analysis of the P1 feed showed no significant difference during storage. The proximate analysis of P2 feed showed no significant difference in ash content, fat content, energy from fat, and total energy during storage; that experienced significant changes were water, protein, and carbohydrate content. The water and carbohydrate content increased on the 1st and 2nd months, while the protein content decreased in the 1st and 2nd months. The analysis results of fatty acids DHA, EPA, AA, and n-3 HUFA did not show significant change during the storage of the two types of feed. The conclusion was that P1 feed had more stable chemical properties than P2 feed after two months of storage. However, the P1 feed was physically more crumbly than the P2 feed.